2017
DOI: 10.1002/jsfa.8592
|View full text |Cite
|
Sign up to set email alerts
|

Application of new insoluble dietary fibres from triticale as supplement in yoghurt – effects on physico‐chemical, rheological and quality properties

Abstract: Insoluble triticale fibre could therefore be used as a supplement to produce functional yoghurt. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…No differences ( P > 0.05) were found at 50, 100 and 150 s ‐1 , while at 200 s ‐1 , the E2 sample presented lower η app than E1 and C. Carrot fibre addition did not affect the η app at low shear rates, but the η app decreased at high shear rates for the sample with higher fibre addition. Same results were found by Miocinovic et al () for yogurt with triticale fibre addition. This decrease in η app value can be attributed to a decrease in the protein aggregate interactions because of the fibre presence.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…No differences ( P > 0.05) were found at 50, 100 and 150 s ‐1 , while at 200 s ‐1 , the E2 sample presented lower η app than E1 and C. Carrot fibre addition did not affect the η app at low shear rates, but the η app decreased at high shear rates for the sample with higher fibre addition. Same results were found by Miocinovic et al () for yogurt with triticale fibre addition. This decrease in η app value can be attributed to a decrease in the protein aggregate interactions because of the fibre presence.…”
Section: Resultssupporting
confidence: 86%
“…The pH changes during fermentation and the pH values, titratable acidity, chemical composition, WHC and microbiological counts of the yogurt after 7 days are shown in Table . The evolution of pH during the fermentation was similar for different yogurts, and in all cases, the fermentation process lasted about 4 h; an exception occurred at 3 h in which experimental yogurts had minor pH values than C. In the same way, Miocinovic et al () did not find changes in the pH evolution during fermentation by the addition of triticale insoluble fibre in the yogurt formulation. Contrary, McCann et al () reported that the addition of carrot particles (from 0.5% to 2.0%) accelerated the acidification rate and the fermentation time decreased by almost 1 h.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The presence of insoluble fiber causes more syneresis because it does not incorporate within a protein network. (Miocinovic et al, ). An increasing trend was observed with storage time in all yogurt samples, probably due to severe casein network rearrangements promoting whey expulsion (Ramirez‐Santiago et al, ).…”
Section: Resultsmentioning
confidence: 99%